PENINGKATAN KUALITAS PEMBELAJARAN SERTA AKTIFITAS BELAJAR SISWA PADA PELAJARAN PKN MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE BERMAIN KOCOK DADU DI SMP NEGERI 5 KOTA SERANG - Komariah, Komariah (Tarbawi, 2018)
Teaching and learning activities at school should be interesting and funny, student activities as learning is always enthusiastic in following each subject. But the reality in the field shows another, learning activities that should attract, full of activities, creativity and bright ideas that do not exist, there is only a passive class hanayalah. Teachers are the spearhead in the success of teaching and learning process, therefore teachers are required to be able to innovate and master the various methods in delivering learning meteri that will be conveyed to the students. Lack of variation in the model of learning is one of the factors lazy students in following the teaching and learning process resulting in the level of mastery of student learning. To cultivate the spirit, cheerfulness in learning and not boring required a method of learning such as "shake the dice" as one of the active learning model, is essentially a traditional game with the aim that students in implementing learning is not saturated because this learning invites students to play while learning. Keywords. Learning Activity, Learning Model, Beat Dice